Glorifying the Simple Life Analyses of Socio-Psychological Constructs in the Context of Reality TV - Hammes, Eva Katharina (Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2016)
The analysis identifies the four socio-psychological constructs identification with a media character, schadenfreude, social comparison, and vicarious embarrassment, as important responses in the context of reality TV. Besides numerous determinants, these constructs are also linked to consequences. In particular, Eva Katharina Hammes identifies schadenfreude and identification as positive responses for the viewer. Vicarious embarrassment is found to be a rather complex response that elicits diverse consequences. Social comparison with its upward and downward forms was found to be very important during the consumption of reality TV programs and also serves as a moderator for the relationship between the identified determinants and associated socio-psychological constructs. Contents • Theoretical Foundations of Mass Media Motivations • Definition and Characteristics of Reality TV • Experimental Studies on Social Motives of Reality TV Target Groups • Teachers and students of media management, social psychology, media psychology, and marketing • Executives and consultants in the field of media management About the Author Eva Katharina Hammes studied Information Management at the University of Koblenz-Landau. After receiving her master's degree, she joined the working group for Media and Service Management at the University of Koblenz-Landau as a doctoral student. In September 2015, Eva Katharina Hammes joined the Chair of General Management and Marketing of the Friedrich-Schiller-University in Jena as a research assistant. <.